Binding Constant: Fluorescence Quenching of Ciprofloxacin with Fe(III) and Zn(II) - Siddiqi, K.S.; Mohd, Ayaz; Aslam, Aftab; Khan, Parwaz; Bano, Shaista (Asian Journal of Chemistry, 2010)
Absorbance and fluorescence spectral pattern of ciprofloxacin in absence and presence of Fe(III) and Zn(II) has been studied at room temperature and under physiological condition. The fluorescence spectra of the drug in presence of the different quantities and different concentrations of the Fe(III) and Zn(II) showed the quenching of ciprofloxacin. It was observed that with increasing quantity of the quencher the emission intensity decreases with negligible variation in the peak position. The absorption spectra of the drug at different pH exhibits two isosbestic points at 320 and 350 nm indicating the presence of three chemical species in solution. The ratio of the two reacting components, the drug and the metal ions was determined by absorption and fluorescence spectro-photometrically.